2014
DOI: 10.1007/s10035-014-0502-8
|View full text |Cite
|
Sign up to set email alerts
|

DEM of triaxial tests on crushable cemented sand

Abstract: Using the discrete element method, triaxial simulations of cemented sand consisting of crushable particles are presented. The triaxial model used features a flexible membrane, allowing realistic deformation to occur, and cementation is modelled using inter-particle bonds. The effects of particle crushing are explored, as is the influence of cementation on the behaviour of the soil. An insight to the effects that cementation has on the degree of crushing is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Aursudkij et al [6] also performed large scale triaxial tests on limestone particles under confining stresses of 10, 30 and 60 kPa and the sample with lowest confining stress was found to give the largest amount of dilation but the smallest amount of breakage. Additionally, as a powerful numerical tool to understand the micromechanical behaviour of granular material, the discrete element method (DEM) [10] has shown some success in simulating triaxial tests on granular materials [11][12][13][14][15][16][17][18][19]. However, it is a challenge to consider both irregular particle shape and ballast degradation in DEM modelling of railway ballast; e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Aursudkij et al [6] also performed large scale triaxial tests on limestone particles under confining stresses of 10, 30 and 60 kPa and the sample with lowest confining stress was found to give the largest amount of dilation but the smallest amount of breakage. Additionally, as a powerful numerical tool to understand the micromechanical behaviour of granular material, the discrete element method (DEM) [10] has shown some success in simulating triaxial tests on granular materials [11][12][13][14][15][16][17][18][19]. However, it is a challenge to consider both irregular particle shape and ballast degradation in DEM modelling of railway ballast; e.g.…”
Section: Introductionmentioning
confidence: 99%
“…de Bono et al studied the effect of cementation on the degree of crushing using the discrete element method. It was shown that in the cemented material, an increase in the degree of crushing was observed with increasing cement content [22]. Shen et al were developed a three-dimensional bonded contact model to simulate the mechanical behavior of bonded granular material using the DEM.…”
Section: Distinct Element Methodsmentioning
confidence: 99%
“…Different contact bond models have been proposed in an attempt to simulate the behaviour of the bond that exists between the cemented material and the soil particles. Examples of contact bond models used to simulate the behaviour of MICP-cemented soils include the parallel bond model (PBM) [49, 50, 143-145, 149, 150], the beam model (BM) [147], the cement ring bond model (CRBM) [47,48,143,144,151], the cohesive bond model (CBM) [152,153] and the serial bond model (SBM) [146].…”
Section: Dem Modellingmentioning
confidence: 99%
“…In general, DEM modelling of chemically cemented soils (e.g., Portland cement) has been investigated by several researchers [140][141][142][143][144][145][146]. Some studies have attempted to also model the micro-scale behaviour of MICP-cemented soils using DEM [47][48][49][50].…”
Section: Dem Modellingmentioning
confidence: 99%